2015
DOI: 10.1021/acs.jpclett.5b01327
|View full text |Cite
|
Sign up to set email alerts
|

Pseudohalide (SCN)-Doped MAPbI3 Perovskites: A Few Surprises

Abstract: Pseudohalide thiocyanate anion (SCN(-)) has been used as a dopant in a methylammonium lead tri-iodide (MAPbI3) framework, aiming for its use as an absorber layer for photovoltaic applications. The substitution of SCN(-) pseudohalide anion, as verified using Fourier transform infrared (FT-IR) spectroscopy, results in a comprehensive effect on the optical properties of the original material. Photoluminescence measurements at room temperature reveal a significant enhancement in the emission quantum yield of MAPbI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
93
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(100 citation statements)
references
References 36 publications
7
93
0
Order By: Relevance
“…With such high content of S, their XRD diffraction patterns are different from the conventional MAPbX 3 structure and many peaks are denoted as planesf or MAPb(SCN) 2 I. [15,17] Figure 3A shows the UV/Vis spectra for Pb(SCN) 2 ,P bI 2, MAPb(SCN) x I 3Àx ,a nd MAPbI 3 .T he absorption onset for the yellow film of PbI 2 is at 520 nm, which is well matchedw ith previousr eports. [13,14] Whereas ar ecent high efficiency SCN pseudohalide perovskite solar cell using DMF/DMSO as co-solvent in one-step spin-coating showed that only trace amount of Sc an be observed by SIMS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With such high content of S, their XRD diffraction patterns are different from the conventional MAPbX 3 structure and many peaks are denoted as planesf or MAPb(SCN) 2 I. [15,17] Figure 3A shows the UV/Vis spectra for Pb(SCN) 2 ,P bI 2, MAPb(SCN) x I 3Àx ,a nd MAPbI 3 .T he absorption onset for the yellow film of PbI 2 is at 520 nm, which is well matchedw ith previousr eports. [13,14] Whereas ar ecent high efficiency SCN pseudohalide perovskite solar cell using DMF/DMSO as co-solvent in one-step spin-coating showed that only trace amount of Sc an be observed by SIMS.…”
Section: Resultsmentioning
confidence: 99%
“…[9,10] Noh et al reported that mixed halidesw ith high Br/I ratios (0.20-0.29) can improves tability significantly at high relativelyh umidity (> 55 %). [15] The impact of thiocyanate on structure stabilityr esults from the favorable thermodynamic properties of large formation constant between Pb and SCN. [11] Therefore, some alternative perovskite structures to replace MAPbI 3 shouldb ed evelopedt oe nhance the stability of the solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…Halder et al claimed that the doped SCN − has brought about an optical band gap increase as well higher PL emission quantum yield. [192] 5. Dual/Triple-Site Mixed PVSK Motivated by the need to improve stability and PCE of PSCs, more complex combinations of ABX 3 hybrid PVSK have been explored, namely, mixed-A/mixed-X, mixed-A/mixed-B, mixed-A/mixed-B/mixed-X PVSK.…”
Section: F − or Pseudohalide/i Mixed Pvskmentioning
confidence: 99%
“…Due to its similar ionic radius of 0.215-0.220 nm for SCN − compared to 0.22nm for I − , this pseudohalogen can replace a "true halide" such as the I − halogen ion. 111,112 The partial halide substitution, forming a MAPbI 3−x (SCN) x perovskite structure, have had a beneficial impact on grain sizes and trap density, 111 optoelectronic properties, 113 and most importantly on its material stability. [114][115][116] In the case of MAPb(SCN) 2 I, the interaction between Pb 2+ and SCN − is much stronger than in the case of neat MAPbI 3 .…”
mentioning
confidence: 99%